Development and characterization of an active chitosan-based film containing quercetin - Souza, M. (2015)
This work aims at developing an active chitosan film through the incorporation of quercetin and the evaluation of physical and functional properties of the films made thereof. The addition of quercetin showed to influence films properties in terms of surface morphology, tensile strength, and opacity while elongation-at-break, thickness, water vapor, and oxygen permeability were not significantly affected with incorporation of quercetin. The color parameters of chitosan films were affected by quercetin incorporation with a decrease of the values of L* and a*. The film exhibited a high free-radical scavenging activity, showing antioxidant activity. The film-forming solutions of chitosan with or without quercetin showed antibacterial activity against four Gram-negative and three Gram-positive bacteria. These results showed that quercetin incorporation in chitosan-based films has potential to be used as a solution for active food packaging.